2018
DOI: 10.1007/s00296-018-4093-2
|View full text |Cite
|
Sign up to set email alerts
|

The efficiency of inspiratory muscle training in patients with ankylosing spondylitis

Abstract: Ankylosing spondylitis (AS) is an inflammatory rheumatic disease affecting mainly the axial skeleton and sacroiliac joints. The aim of the current study was to investigate the effects of inspiratory muscle training (IMT) on respiratory muscles and functional exercise capacity, as well as on the specific outcomes of the disease in AS patients. A total of 32 AS patients (mean age 37.37 ± 10.41 years) were randomly assigned as the Training Group (TG) (n = 16, mean age = 35.62 ± 8.18 years) who received IMT + conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…In one study in AS patients inspiratory muscle training was added to conventional exercises. This led as expected to increased inspiratory muscle strength, but also to increased functional exercise capacity and decreased disease activity [21]. In PsA patients, high intensity interval training for 11 weeks did not change the disease activity as measured by DAS44 [22], and resistance training for 12 weeks did not influence the DAS28 but did decrease disease activity as measured by BASDAI and increased functional capacity and quality of life, however without a measurable difference in muscle strength [23].…”
Section: The Benefits Of Exercise In Spa Patientsmentioning
confidence: 54%
“…In one study in AS patients inspiratory muscle training was added to conventional exercises. This led as expected to increased inspiratory muscle strength, but also to increased functional exercise capacity and decreased disease activity [21]. In PsA patients, high intensity interval training for 11 weeks did not change the disease activity as measured by DAS44 [22], and resistance training for 12 weeks did not influence the DAS28 but did decrease disease activity as measured by BASDAI and increased functional capacity and quality of life, however without a measurable difference in muscle strength [23].…”
Section: The Benefits Of Exercise In Spa Patientsmentioning
confidence: 54%
“…In both groups, control or true load, there was a significant increase in inspiratory and expiratory muscle strength at the end of the training protocol, improvement in volumetric capnography variables, exercise tolerance and reduction of dyspnea in performing daily life activities. Regarding respiratory muscle strength, although the effects of the IMT on patients with sickle cell disease have been poorly studied, 14 studies conducted on individuals with chronic obstructive pulmonary disease (COPD), 10 older women 26 or those with ankylosing spondylitis 11 showed an increase in the PImax and PEmax after the termination of the training protocol. Ciesla 27 includes the IMT as one of the types of breathing exercises and points out several benefits in these exercises, as it improves thoracic-cage mobility, increased tidal volume and increased inspiratory capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Inspiratory muscle training (IMT) has been shown to be an efficient method of improving exercise tolerance and inspiratory and expiratory muscle strength in a number of diseases. 10 , 11 Some studies have shown that IMT even enables increased oxygen uptake in the blood, decreases the perception of dyspnea and delays the onset of premature fatigue. 12 , 13 However, the effects of IMT on patients with sickle cell anemia are relatively unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In both groups: control or true load, there was a significant increase in inspiratory and expiratory muscle strength at the end of the training protocol, improvement in volumetric capnography variables, exercise tolerance and reduction of dyspnea in performing daily life activities. Regarding respiratory muscle strength, although the effects of IMT in patients with sickle cell disease have been poorly studied (17), studies conducted in individuals with chronic obstructive pulmonary disease (COPD) (13), older women (26) or with ankylosing spondylitis (14) showed an increase in PImax and PEmax after the termination of the training protocol. Ciesla includes IMT as one of the types of breathing exercises and points out several benefits these exercises, as it improves thoracic-cage mobility, increased tidal volume and increased inspiratory capacity (27).…”
Section: Discussionmentioning
confidence: 99%
“…Inspiratory muscle training (IMT) has been shown to be an efficient method of improving exercise tolerance and inspiratory and expiratory muscle strength in a number of diseases (13,14). Some studies have shown that IMT even enables increased oxygen uptake in the blood, decreases the perception of dyspnea and delays the onset of premature fatigue (15,16).…”
mentioning
confidence: 99%